Evaluation As a Type of Research in Islamic Education - Samuji, Samuji (Jurnal Paradigma, 2022)
Evaluation provides benefits for humans in general, and particulas for individuals, through continuous evaluation, all work or program activities that exist in the world of education will be achieved. In other fields in the organizational scale this evaluation is applied, because in the organitation the evaluation or supervision in the final fungtion of each activity. Individual or several people sometimes ignore this evaluation fuction, so that they unwittingly result in the goals that are the expectations of individuals or organizations cannot be achieved optimally due to lack knowing, understanding and appliying this evaluation function. For evaluation as type of research it is necessary to carry out or move in order to provide changes to society and the world of Islamic education. Through this evaluation, we can provide sugestions and constructive criticism on the activities of the program that we have launched. Good changes starts form ourselses, both as students, teachers, lecturers, society, nation and state. If we can evaluate ourselves, then the changes for the good will always be in us. Evaluations is closely related to research and Islamic education where so that the goals of Islamic education can type of Islamic education research.